Motives and visit characteristics of local and foreign visitors in Langkawi - Zameli, Nurul Hikmah; Mohammad Afandi, Syamsul Herman; Samdin, Zaiton; Shuib, Ahmad; Che Ibrahim, Nur Syuhada (2012)
A study on visitors in Langkawi Islands had been conducted in order to get information about visitors’ motives in that area in 2011. This paper is a part of the study that focused on visitors and visit characteristics, visitors’ motives and the comparison of the types of visitors. This study had used a quantitative method where 178 of questionnaires had been distributed to visitors in Langkawi Islands. SPSS was used to analyze the data in this study. Several analyses had been conducted to assess the information of visitors such as, descriptive analyses, to observe the frequencies, means and percentage of visitors’ motives. Mann-Whithey U-test (Two-sample test) was used to compare motives between two variables in this study. There are significant differences of motives between local and foreign visitors. Eleven motives were founded to have significant differences. The study results showed the information of visitors’ characteristics (gender, age, nationality, academic qualifications and professions), visit characteristics (first time visit, visit frequencies and visit group types), information on visitors’ activities and the motives of local and foreign visitors. The findings provide useful information to tourism sectors in Langkawi to maintain and improve their tourism activities in future.